Pengaruh Profitabilitas, Likuiditas, Ukuran Perusahaan dan Struktur Modal terhadap Nilai Perusahaan: (Studi Empiris pada Perusahaan Sektor Properti dan Real Estate yang Terdaftar pada Bursa Efek Indonesia (BEI) Periode 2019 – 2023) - Eko Putranto; Martini Martini (Institut Teknologi dan Bisnis (ITB) Semarang, 2025)
This research was conducted with the aim of analyzing profitability, liquidity, company size and capital structure. This research was conducted on Property and Real Estate Sector Companies listed on the Indonesia Stock Exchange for the 2019- 2023 period. The sampling method in this research used a purposive sampling method with a sample of 40 companies in the property and real estate sector that met the sample criteria. This research uses multiple linear regression analysis techniques and uses the SPSS version 22.0 test tool. The results of this research show that the variables profitability and company size have no effect on company value, while liquidity and capital structure have a negative effect on company value.